Uji Kualitatif Pewarna Rhodamin B Pada Jajanan Anak-Anak Sekolah Di Wilayah Kecamatan Banjarsari - Akhmad Mustofa & Yustina Wuri Wulandari (Exsplorasi, 2011)
ABSTRACTThe Number of school's children were large enough in surakarta. It was a big market potential for various companies and traders to sell their products.